Ophthalmic education and ophthalmologists growth trends in Iran (1979–2016) - Shima Tabatabai (Journal of Ophthalmic & Vision Research, 2019)
Purpose: To analyze the growth trends in ophthalmic education in Iran since 1979, and to discuss their implications on the profession. Methods: This comprehensive national study was performed by the Academy of Medical Sciences of I.R. Iran. The data were gathered from the Specialty Training Council of the Ministry of Health and from the Medical Council of Iran. Results: Our analysis revealed ten important current growth trends and seven future trends and implications. Between 1979-80 and 2015-16, the number of residents annually admitted to ophthalmology increased from 21 to 84 and related fellowships and from 0 to 34. The number of ophthalmologists graduating in the country increased from 21 (45%) in 1979 to 69 (98%) in 2015. The ratio of ophthalmologists per 100,000 people averaged 1.91 in 1979 and 3.00 in 2016. Considering migrant and retired ophthalmologists, there are approximately 2400 active ophthalmologists in Iran. In 1979, there was one active ophthalmologist per 52,112 people; in 2014, there was one per 33,333 people. This represents a per capita increase of 57%. Since 1979, the number of active ophthalmologists has increased by 234%. The number of active women ophthalmologists has increased by more than 600%, from 65 (9%) in 1979 to 470 (20%) in 2016. Conclusion: Equitable geographic distribution and balanced combination of ophthalmologists (women/men and specialists/fellowships) are necessary to optimize community eye health. We propose further studies on the effects of fellowship training growth and work patterns of female and male ophthalmologists.